Essentials Of Financial Accounting - Asish K Bhattacharyya; BHATTACHARYYA (Asish K) (New Delhi Phi Learning Private Limited, 2009)
A knowledge of key accounting concepts and an understanding of corporate financial practices are essential in making good business decisions. This concise book on financial accounting introduces the readers to such accounting concepts in a corporate framework.With a strong user-based approach fortified by practical examples, the author presents a tailor-made textbook to meet the immediate requirement of the MBA curriculum. The contents and the organization of the chapters make the book eminently suitable for short term professional courses on the subject.This book: aims to teach the subject in a simple and jargon-free language; introduces a new chapter devoted to advance accounting concepts; includes a mini-accounting dictionary for ready reference; each section is supplemented by a large number of examples; and, easily understandable even by non-finance professionals.
Keywords: Financial Accounting